Analisis Dampak Penggunaan Pinjaman Online Terhadap Minat Dan Gaya Hidup Konsumtif Masyarakat - Putrilia, Astrid; Fajrin Muharomah, Nur; Kusumah Safitri, Yuniarti; Wahyu, Ahmad (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
The purpose of this research is to identify and study the use of online loan applications that have an impact on people’s interest and comsumtive behavior. This research was conducted through a qualitative approach method or using questionnaires and the number of respondents was only 48 people (exceeding the maximum limit of 30). Online loans are platforms that offer loans or installment payments over the internet without undergoing complicated procedures, helping people who will borrow for needs or just want something online but do not have sufficient funds to do so. The availability of online loans certainly has a positive and negative impact on people’s behavior because it attacts people’s interest. Therefore, the purpose of this study is to analyze how the impact of using online loans in influencing comsumtive lifestyle habits. REFERENSI al., C. N. (2020). Dampak sosial Ekonomi Jerat Utang Rumah tangga di Indonesia. Perkumpulan PRAKARSA. GAP, S., L.A Trupalupi, & L.A Haris. (2014). Analisis Faktor Yang Mempengaruhi Keputusan Nasabah dalam Pengambilan Kredit dalam LPD (Lembaga Pengkreditan Desa) Desa Pakraman Manggissari . Pendidikan Ekonomi, Vol. 4, No.1. Hasibuan, M. (2008). Dasar-Dasar Perbankan. jakarta: Bumi Aksara. Ilaswara, D. (2012-2019). Analisis Pelaksanaan Harbolnas di Indonesia. Sains Manajemen, 1-12. Junaidi, & Sfenrianto. (2015). A Model Factos Influencing Consumer's Intention To Use E-Payment System In Indonesia. 59:214-220. Kotler, & Philip. (2002). Manajemen Pemasaran, Jilid 1, Edisi Milenium. jakarta: Prehallindo. Kusnawan, A., Silaswara, D, Andy, & Sefung, T. (2019). Pengaruh Diskon Pada Aplikasi e-Wallet Terhadap Pertumbuhan Minat Pembelian Impulsif Konsumen Milenial di Wilayah Tangerang. Jurnal Sains Manajemen, 5 No 2 , 137-160. Kusnawan, A., Silaswara, D, Andy, & Sefung, T. (2019). Pengaruh Diskon Pada Aplikasi e-Wallet Terhadap Pertumbuhan Minat Pembelian Impulsif Konsumen Milenial di Wilayah Tangerang. Jurnal Sains Manajemen, 5 No 2 (Desember 2019), 137-160. Moleong, L. J. (2016). Metodologi Penelitian Kualitatif. bandung: PT. Remaja Rosdakarya. Mowen, Jhon C, & Michael Minor. (2002). Consumer Behavior atau Perilaku Konsumen. Jakarta: Erlangga. Poerwanto, N. (2010). Psikolog Pendidikan Bandung:Remaja Rosdakarya. Minat Merpakan Landasan Penting Bagi Seseorang Untuk Melakukan Kegiatan dengan Baik yaitu dorongan seseorang untuk Berbuat. 66. Sardiman. (2011). Interaksi Motivasi Belajar Mengajar. Jakarta: Rajawali Pers. Senada, & Setiadi. (2010). Suarni GAP, 2014. Supriyanto, E., & Ismawati, N. (2019). Sistem Informasi Fintech Pinjaman Online Berbasis Web. Just IT. 100-10